Immutable Digital Timestamp as a Preventive Measure Against Podcast Manipulation: A Normative and Comparative Legal Analysis - Ninik Zakiyah; Budi Santoso; Muh. Afif Mahfud; Try Hardyanthi; Noor Kholifah Hidayati (Universitas Internasional Batam, 2026)
The growth of digital audio content distribution through podcast platforms raises concerns about the authentication and integrity of electronic evidence within Indonesia's legal system. Although the ITE Law recognizes electronic information and documents as valid evidence, it has yet to establish clear technical standards for verifying the integrity and publication date of digital content. This article adopts a normative legal approach, using a comparative method to examine the United States and the European Union. In the United States, the authentication of electronic evidence under Federal Rule of Evidence Rule 901 generally accepts hash verification and chain of custody as reliable methods. Meanwhile, the European Union, through Regulation (EU) No. 910/2014 (eIDAS), has institutionalized qualified electronic timestamps as part of its trust services, providing a presumption of data integrity. This comparison shows that Indonesia still follows a reactive evidentiary model and has not yet implemented preventive technical standards. This article proposes a normative reconstruction that requires immutable timestamps and minimum hash standards for implementing regulations as a form of “regulation by architecture” and “compliance by design.” This approach aims to improve legal certainty and accountability without impeding free expression, making the integrity of digital content an integral part of the national legal framework.